Crystallization behavior of poly(3-hydroxybutyrate) nanocomposites based on modified clays: Effect of organic modifiers - D'amico, David Alberto (2012)
Isothermal and non-isothermal crystallization kinetics of nanocomposites of poly(3-hydroxybutyrate) (PHB) with 4 wt% of montmorillonite Cloisite®Na+ (CNa+) and chemically modified clays Cloisite®15A and 93A (C15A and C93A) prepared by solution casting have been investigated by differential scanning calorimetry. Nanoparticles addition did not significantly affect the crystallinity and melting temperatures of the PHB, regardless the type of clay. Several models such as the Liu-Mo, Avrami, Lauritzen–Hoffman and isoconversional were found to provide a fairly satisfactory description of the crystallization kinetics of PHB and its nanocomposites. The results showed a slight effect of the CNa+ and C93A on the crystallization kinetics parameters of PHB. However, a retarded effect on the crystallization rate of the polymer was found when C15A clay was added. It was attributed to the high dispersion of this clay in the polymer.